Effect of Graphite on the Microstructure and Density of Aluminium Composite AA7075 Using Hot Press Forging - Mohammad Aris, Nurathirah; Mustapa, Mohammad Sukri (Research Progress in Mechanical and Manufacturing Engineering, 2025)
There has been growing interest in developing aluminium composites with improved properties for industrial applications. Aluminium alloy AA7075 is a lightweight material with excellent strength, while graphite enhances lubrication and reduces density. This study aimed to investigate the physical properties of recycled Aluminium AA7075 reinforced with 2.5% Graphite powder through a hot press forging method and compare its performance with AA6061 reinforced with 2.5% Graphite, known for its high strength. Density measurements were performed using the Archimedes principle, and the microstructure was analyzed using Optical Microscopy and Scanning Electron Microscopy (SEM). The findings reveal that the addition of graphite improves microstructural uniformity and reduces density. Comparatively, AA6061-2.5% Graphite exhibited superior strength, highlighting its potential for applications requiring both high-performance and lightweight materials. This study underscores the viability of sustainable recycling methods in producing advanced composite materials with enhanced properties for industrial applications